1996
DOI: 10.1177/088307389601100506
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Neonatal Seizures With Carbamazepine

Abstract: Carbamazepine has been used in adults and children for over 30 years. In spite of an excellent therapeutic and side-effect profile in older children, it has never been used as a primary anticonvulsant in neonates. This is the first report of the long-term use of carbamazepine in neonates. Ten full-term neonates with two or more seizures due to hypoxic-ischemic encephalopathy were given 10 mg/kg of carbamazepine as a loading dose via nasogastric tube. Twenty-four hours later, the first five patients began a mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…Eight newborns and two older infants received CBZ at a dose of 5±8 mg/kg twice daily. Resorption and ecacy of CBZ were excellent in both studies [6,14] and no adverse eects were observed. It is still possible that in one or the other of our patients, symptoms were not interpreted as an adverse eect of CBZ treatment because it was not the only drug used at the same time in intensively treated and often mechanically ventilated patients.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Eight newborns and two older infants received CBZ at a dose of 5±8 mg/kg twice daily. Resorption and ecacy of CBZ were excellent in both studies [6,14] and no adverse eects were observed. It is still possible that in one or the other of our patients, symptoms were not interpreted as an adverse eect of CBZ treatment because it was not the only drug used at the same time in intensively treated and often mechanically ventilated patients.…”
Section: Discussionmentioning
confidence: 89%
“…CBZ has been studied prospectively by others [14] as a monotherapy in ten infants. Therapy was continued for 3 to 9 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While lidocaine is also a sodium-channel blocker, concerns about cardiac toxicity have limited its use in the NICU, even though a recent study showed the drug to be effective and safe in a large number of newborns [24]. CBZ is rarely used in the NICU [25,26]. However, oral CBZ has recently been reported to be a safe and effective AED to control seizures in infants with KCNQ2-related epilepsy, both BFNS and KCNQ2 encephalopathy [10,11,13], and sodium channel blockers are now recommended as established precision medicine treatment in these disorders [27].…”
Section: Discussionmentioning
confidence: 99%
“…at ASPET Journals on May 12, 2018 dmd.aspetjournals.org in vitro, the elimination half-life of CBZ was reported about 24 h at neonatal period (Singh et al, 1996). It is no inferiority in that of the adult.…”
Section: Effects Of Endogenous Steroids On Cyp3a4 and Cyp3a7 Activitymentioning
confidence: 99%